Risk Factors Causing Myocardial Infarction Among Young and Middle-Aged Populations: A Literature Review (International Journal of Physiotherapy, 2025)
Background: Myocardial infarction is the principal cause of morbidity and mortality on a global scale, increasingly affecting the young and middle-aged population. Through a comprehensive approach, the goal was to reduce the burden of myocardial infarction and enhance the life span of individuals. Hence, this literature review aims to analyze the global risk factors of myocardial infarction among the young and middle–aged population.Methods: An analysis from major data repositories like PubMed, Google Scholar, and Science Direct was retrieved, which targeted publications from 2019 to 2023. Studies were selected based on predefined inclusion criteria and encompassing various study designs.Results: Out of 400 articles, 19 articles met the inclusion criteria. Risk factors found from this review were classified into physical, psychological, social, genetic, and underlying health components. Each category was further divided into modifiable and non-modifiable risk factors.Conclusion: This literature review provides an overview of the various global risk factors causing myocardial infarction in a young and middle-aged population. These risk factors are categorized into modifiable and non-modifiable risk factors. Thus, identifying modifiable risk factors is essential for preventive strategies, early detection, and treatment interventions, as well as to create awareness for improving life spans in the young and middle-aged population.